D4‑Symmetric Dirhodium Tetrakis(binaphthylphosphate) Catalysts for Enantioselective Functionalization of Unactivated C–H Bonds - Chen, Ziyi; Shimabukuro, Kristin; Bacsa, John; Musaev, Djamaladdin G.; Davies, Huw M. L. (Journal of the American Chemical Society, 2024)
Dirhodium tetrakis(2,2′-binaphthylphosphate) catalysts were successfully developed for asymmetric C–H functionalization with trichloroethyl aryldiazoacetates as the carbene precursors. The 2,2′-binaphthylphosphate (BNP) ligands were modified by introduction of aryl and/or chloro functionality at the 4,4′,6,6′ positions. As the BNP ligands are C2-symmetric, the resulting dirhodium tetrakis(2,2′-binaphthylphosphate) complexes were expected to be D4-symmetric, but X-ray crystallographic and computational studies revealed this is not always the case because of internal T-shaped CH−π and aryl–aryl interactions between the ligands. The optimum catalyst is Rh2(S-megaBNP)4, with 3,5-di(tert-butyl)phenyl substituents at the 4,4′ positions and chloro substituents at the 6,6′ positions. This catalyst adopts a D4-symmetric arrangement and is ideally suited for site-selective C–H functionalization at unactivated tertiary sites with high levels of enantioselectivity, outperforming the best dirhodium tetracarboxylate catalyst developed for this reaction. The standard reactions were conducted with a catalyst loading of 1 mol % but lower catalyst loadings can be used if desired, as illustrated in the C–H functionalization of cyclohexane in 91% ee with 0.0025 mol % catalyst loading (29,400 turnover numbers). These studies further illustrate the effectiveness of donor/acceptor carbenes in site-selective intermolecular C–H functionalization and expand the toolbox of catalysts available for catalyst-controlled C–H functionalization.